2018
DOI: 10.26417/ejed.v1i1.p36-48
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education in Bangladesh: Digging Deeper into Educational Prospects of Children with Disabilities in Bangladesh

Abstract: This paper explores multiple dimensions of inclusive education in Bangladesh's targeted schools. It compares the educational performance of children with disabilities to children without disabilities analysing their participation, retention and school completion rates. Through quantitative and qualitative analysis, it tries to explore the existing inclusive education practices at school level for quality and learning. The study uses community resource mapping, open-ended interviews, field observations, a quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In consonance with SDGs (Goal 4) (building inclusive learning environments), the Act puts great emphasis on accessible built environments in public premises. Evidence, however, suggests that public premises such as roads, schools, and public transportation are mostly inaccessible, and this can deter CWDs from participating in the mainstream society in Bangladesh ( Nuri et al, 2019 ; Zulfiqar et al, 2018 ). There is not a specific budget allocation to make the built environment (e.g., roads, highways, footpaths, footbridges, and public transport) disability-friendly ( Jahan, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In consonance with SDGs (Goal 4) (building inclusive learning environments), the Act puts great emphasis on accessible built environments in public premises. Evidence, however, suggests that public premises such as roads, schools, and public transportation are mostly inaccessible, and this can deter CWDs from participating in the mainstream society in Bangladesh ( Nuri et al, 2019 ; Zulfiqar et al, 2018 ). There is not a specific budget allocation to make the built environment (e.g., roads, highways, footpaths, footbridges, and public transport) disability-friendly ( Jahan, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact on their educational development is frequently significant, severely limiting their growth potential. According to a survey, only 4% of an estimated 1.6 million children with impairments of primary school age had access to schooling (Zulfiqar et al, 2018). In another survey it was found that, slightly more than half of people with disabilities have no formal education (54.74 percent), while 23.11 percent have primary (I-V) education and 18.33 percent have secondary (VI-XII) education.…”
Section: Children With Disabilities and Their Educationmentioning
confidence: 99%
“…As per the Sustainable Development Goal (SDG) 4, the target for all developing countries is to ensure an equitable, inclusive, and quality education system for all children by 2030 All countries around the world, including Bangladesh, are working to remove inequities and barriers to access and quality education (Zulfiqar et al, 2018). Bangladesh is a signatory to and active participant in many international declarations, conventions, and charters, including the Universal Declaration of Human Rights, UN Convention on the Rights of the Child, Jomtien Declaration(1990), UN Standard Rules on the Equalization of Opportunities for Persons with Disabilities (1993), Salamanca Declaration on Inclusive Education (1994), Dakar Framework (2000, United Nations Convention on the Rights of Persons with Disability (UNCRPD) (2006).…”
Section: Legal Framework For Education Of Children With Disabilitiesmentioning
confidence: 99%